Disparities in use of skilled birth attendants and neonatal mortality rate in Guinea over two decades - Betregiorgis Zegeye; Bright Opoku Ahinkorah; Edward Kwabena Ameyaw; Eugene Budu; Abdul-Aziz Seidu; Comfort Z. Olorunsaiye; Sanni Yaya (BMC, 2022)
Abstract Background Maternal mortality remains high in sub-Saharan African countries, including Guinea. Skilled birth attendance (SBA) is one of the crucial interventions to avert preventable obstetric complications and related maternal deaths. However, within-country inequalities prevent a large proportion of women from receiving skilled birth attendance. Scarcity of evidence related to this exists in Guinea. Hence, this study investigated the magnitude and trends in socioeconomic and geographic-related inequalities in SBA in Guinea from 1999 to 2016 and neonatal mortality rate (NMR) between 1999 and 2012. Methods We derived data from three Guinea Demographic and Health Surveys (1999, 2005 and 2012) and one Guinea Multiple Indicator Cluster Survey (2016). For analysis, we used the 2019 updated WHO Health Equity Assessment Toolkit (HEAT). We analyzed inequalities in SBA and NMR using Population Attributable Risk (PAR), Population Attributable Fraction (PAF), Difference (D) and Ratio (R). These summary measures were computed for four equity stratifiers: wealth, education, place of residence and subnational region. We computed 95% Uncertainty Intervals (UI) for each point estimate to show whether or not observed SBA inequalities and NMR are statistically significant and whether or not disparities changed significantly over time. Results A total of 14,402 for SBA and 39,348 participants for NMR were involved. Profound socioeconomic- and geographic-related inequalities in SBA were found favoring the rich (PAR = 33.27; 95% UI: 29.85-36.68), educated (PAR = 48.38; 95% UI: 46.49-50.28), urban residents (D = 47.03; 95% UI: 42.33-51.72) and regions such as Conakry (R = 3.16; 95% UI: 2.31-4.00). Moreover, wealth-driven (PAF = -21.4; 95% UI: −26.1, −16.7), education-related (PAR = -16.7; 95% UI: −19.2, −14.3), urban-rural (PAF = -11.3; 95% UI: −14.8, −7.9), subnational region (R = 2.0, 95% UI: 1.2, 2.9) and sex-based (D = 12.1, 95% UI; 3.2, 20.9) inequalities in NMR were observed between 1999 and 2012. Though the pattern of inequality in SBA varied based on summary measures, both socioeconomic and geographic-related inequalities decreased over time. Conclusions Disproportionate inequalities in SBA and NMR exist among disadvantaged women such as the poor, uneducated, rural residents, and women from regions like Mamou region. Hence, empowering women through education and economic resources, as well as prioritizing SBA for these disadvantaged groups could be key steps toward ensuring equitable SBA, reduction of NMR and advancing the health equity agenda of "no one left behind."